Métodos de manejo na cultura da figueira em condições semiáridas - Moura, Elias Ariel de (Universidade Federal Rural do Semi-Árido, 2020)
Due to the great adaptability of the fig tree in adverse conditions, the semiarid becomes an excellent productive opportunity for this culture, however needing technologies that exploit the potential of the culture in atypical conditions. Thus, the present study aimed to seek technologies for the conduction system and management methods for the cultivation of fig trees in semi-arid conditions. Two experiments were carried out: The first in the didactic orchard of UFERSA, in the years 2018 to 2020. During the experiment, 4 irrigation depths (ETc%) and 4 potassium doses were applied. The design was in randomized blocks, in a subdivided plot with 3 blocks and 2 plants per plot. The plots consisted of irrigation depths (50, 75, 100 and 125% ETc), the subplots the potassium doses (0, 60, 120 and 240 g plant-1 ) and the sub-plot of the production cycle (18/19 and 19/20). The second was held at the Fazenda Experimental da Ufersa, Rafael Fernandes in 2019. During the experiment, 4 conduction systems were applied in organic and conventional systems. The design was in randomized blocks, in a 4 x 5 factorial scheme, with 3 blocks and 3 plants per plot. The factors were the 4 conduction systems (2 legs, 3 legs, 4 legs and trellis system) and 5 cultivation systems (organic with sources: chicken bed, sheep manure, bovine manure and organic compost; and conventional with source: mineral - NPK). The characteristics evaluated in both experiments were: Production, number of fruits, fruit length and diameter, average fruit mass, fruit firmness, fruit color index, on the L * luminosity scale, C * chromaticity and hue angle ° Hue , soluble solids of the fruits, titratable acidity, hydrogen potential, SS / AT ratio and vitamin C of the fruits. For the first experiment, the water deficit and excess significantly reduce the production and number of fig fruits due to the cumulative effect. The water deficit and excess with high doses of potassium cause reductions in fruit size. The fruits were higher in the intermediate doses (60 to 120 g plant-1 ) together with the water depth up to 107.93% ETc. The highest values of fruit firmness were obtained at a dose of 120 g plant1 in Li of 103.75% ETc. The fruits showed increases in the superior organoleptic qualities in the subsequent cycles, with increases in the levels of soluble solids and decreases in the titratable acidity and pH of the fruits. The water deficit causes significant increases in the vitamin C content of the fruits. For the second experiment, organic cultivation using the chicken litter source showed production, productivity, number of fruits and firmness similar to conventional cultivation. The driving systems with 3 kicks, 4 kicks and trellis showed fruits with better organoleptic qualities. Organic cultivation using organic compost showed smaller fruit sizes.
Keywords: Déficit hídrico; Ficus carica L.; Evapotranspiração da cultura; Fontes orgânicas; Qualidade organoléptica; Water deficit; Ficus carica L.; Crop evapotranspiration; Organic sources; Organoleptic quality; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA